Integration of Local Wisdom in Religious Character Education: A Study of the 'Gawe Batigo' Tradition - Permaisuri, Bunga; Candra, Hadi (Ishlah: Jurnal Ilmu Ushuluddin, Adab dan Dakwah, 2024)
This study aims to analyze the reinforcement of religious character values based on local wisdom through the Gawe Batigo tradition in Koto Payang, Koto Tuo, and Semumu villages. The background of this research arises from the low interest and courage of the community in leading congregational prayers, resulting in the prayers often being led by the same group of people. The Gawe Batigo tradition is expected to enhance religious character and cultivate new imams in these villages. This research employs a qualitative approach with an ethnographic method. Data were obtained from primary sources through interviews with customary leaders (Depati) and Islamic scholars, and from secondary sources through relevant documentation. Data collection techniques included observation, interviews, and documentation. Data analysis was conducted through data categorization, reduction, presentation, and conclusion drawing. The results indicate that the implementation of Gawe Batigo follows structured stages, including duduk busamo, ngimboa guru, bapacau (trial), batanteik, baarak-arak, prayer performance, and ngantoa ima. The religious character values strengthened through this tradition include worship, morality, discipline, trustworthiness, sincerity, and exemplary behavior. Positive impacts include the formation of future generations such as imams, increased religious knowledge, and reinforcement of congregational prayer practices in the mosque. The negative impact identified is limited rest time for prospective participants, particularly during Ramadan, due to mandatory training sessions.